Dependency Between Grammatical Structure of Language and Verbal Thinking Strategies - Ekaterina V. Savitskaya (Publishing house "Sreda", 2020)
The article contains a discussion of how the grammatical structure of a language determines sentence structure and affects verbal thinking strategy. The stages of languages' historic development (incorporative, ergative, nominative) and the relationship between sentence structure and native speakers' thinking are characterized. The common case of the grammatical subject of a sentence does mean that Anglo-Saxons regard themselves as their own fortune's active makers and masters. The common case equally expresses success and failure, activity and passivity, self-will and conformity. Nowadays, languages of all the three types coexist on the Globe. The languages of the first two types are used not only by primitive peoples but also by civilized nations. But this does not mean that civilized speakers think archaically. Methods and conclusions. Contrastive analysis of language material (English personal and Russian impersonal morphosyntactic constructions) enables the author to conclude: there is no direct correlation between national character and sentence structure. The connection between thinking and grammar does not consist in this; it consists in the choice of thinking strategies based on the grammatical potential of the language under discussion.